THE EFFECT OF ACQUIRING FIRM’S GROWTH OPPORTUNITY ON THE VALUE RELEVANCE OF GOODWILL - Shirabe, Yuji (Accounting Department,, 2016)
In recent years, mergers and acquisitions (M&A) have become increasingly important for Japanese firms to achieve growth. In this situation, how does the stock market recognize and evaluate the goodwill generated as a consequence of M&A? Given that Japanese companies have increasingly used M&A as for a tool for growth, we can say that the growth opportunity of the acquiring firms is an important factor that affects valuation of goodwill in the stock market. In this study, we investigate the link between growth opportunity and the value of goodwill in the stock market.The results of our study show that the market valuation of newly acquired goodwill is positively influenced by the growth opportunities of acquiring firms in Japan. Therefore, this study implies that M&A works better when it is done to utilize internal growth opportunity rather than to incorporate external growth opportunities into the firm.